Dogs can be trained to find a bar magnet - Martini, Sabine; Begall, Sabine; Findeklee, Tanja; Schmitt, Marcus; Malkemper, E Pascal; Burda, Hynek (PeerJ, 2018)
Magnetoreception, the ability to sense the Earth's magnetic field (MF), is a widespread phenomenon in the animal kingdom. In 1966, the first report on a magnetosensitive vertebrate, the European robin (Erithacus rubecula), was published. After that, numerous further species of different taxa have been identified to be magnetosensitive as well. Recently, it has been demonstrated that domestic dogs (Canis lupus familiaris) prefer to align their body axis along the North-South axis during territorial marking under calm MF conditions and that they abandon this preference when the Earth's MF is unstable. In a further study conducting a directional two-choice-test, dogs showed a spontaneous preference for the northern direction. Being designated as putatively magnetosensitive and being also known as trainable for diverse choice and search tests, dogs seem to be suitable model animals for a direct test of magnetoreception: learning to find a magnet. Using operant conditioning dogs were trained to identify the MF of a bar magnet in a three-alternative forced-choice experiment. We excluded visual cues and used control trials with food treats to test for the role of olfaction in finding the magnet. While 13 out of 16 dogs detected the magnet significantly above chance level (53-73% success rate), none of the dogs managed to do so in finding the food treat (23-40% success rate). In a replication of the experiment under strictly blinded conditions five out of six dogs detected the magnet above chance level (53-63% success rate). These experiments support the existence of a magnetic sense in domestic dogs. Whether the sense enables dogs to perceive MFs as weak as the Earth's MF, if they use it for orientation, and by which mechanism the fields are perceived remain open questions.
Keywords: Operant conditioning; Behavioral test; Magnetoreception; Domestic dogs